Evaluating the effects of two different kinesiology taping techniques on shoulder range of motion and proprioception in patients with hypermobile Ehlers–Danlos syndrome: a randomized controlled trial - Tudini, Frank; Jordon, Max; Levine, David; Healy, Michael; Cathey, Sarah; Chui, Kevin (Frontiers in Rehabilitation Sciences, 2024)
Background Ehlers–Danlos syndrome (EDS) is a common group of inherited connective tissue disorders with a prevalence as high as 0.75%–2% of the population. Physical manifestations include pain and decreased proprioception, especially in more mobile joints, such as the shoulder. The kinesiology tape (K-Tape) is often used to treat patients with shoulder dysfunction. The effectiveness of the K-Tape is uncertain, and there is a lack of studies specifically studying the K-Tape in an EDS population. Purpose The purpose of this study was to compare the short-term effects of two different K-Tape procedures on shoulder active joint reposition (AJR) and active range of motion (AROM) in patients with hypermobile EDS (hEDS) and shoulder pain. Methods All participants were recruited from the EDS support groups and presented with shoulder pain. Baseline demographic information was obtained for each participant, after which AROM and AJR were assessed. The participants were randomized to receive one of two K-Tape procedures. Testing was repeated immediately post-taping and 48 h post-taping. Results Significant improvements in shoulder external (F = 10.917, p < 0.001) and internal (F = 11.736, p < 0.001) rotations were seen from baseline to immediately post-taping and baseline to 48 h post-taping in the experimental K-Tape group. There were no significant differences in the shoulder rotation in the control K-Tape group and no significant differences in either group for shoulder flexion or AJR at any time point (p > 0.05). Conclusion K-Tape may offer short-term improvements in shoulder rotation AROM in patients with hEDS and shoulder pain.